2004
DOI: 10.1002/jctb.1157
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of lipase production by Geotrichum candidum in stirring and airlift fermenters

Abstract: The production of lipase by Geotrichum candidum in both, stirred tank and airlift bioreactors were compared. G candidum an imperfect filamentous fungus, grows well in liquid medium, and produces a lipase with specific affinity for long-chain fatty acids with cis-9 double bonds but, lipase production is generally not efficient because the optimum medium composition and fermentation conditions are not known. Response surface methodology was used to optimize the agitation speed (100-500 rpm) and aeration (0.2-1.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 25 publications
3
51
1
2
Order By: Relevance
“…Dependent variables flavor, texture and overall liking were analyzed by multivariate regressions and significances of the models were tested (Burkert et al, 2005) quadratic model terms while sugar caused no influence (p > 0.05) in these terms. A better understanding of the influence of the sensory descriptive attributes on the açaí samples with different concentrations of guaraná and sugar would be achieved applying a descriptive technique.…”
Section: Resultsmentioning
confidence: 99%
“…Dependent variables flavor, texture and overall liking were analyzed by multivariate regressions and significances of the models were tested (Burkert et al, 2005) quadratic model terms while sugar caused no influence (p > 0.05) in these terms. A better understanding of the influence of the sensory descriptive attributes on the açaí samples with different concentrations of guaraná and sugar would be achieved applying a descriptive technique.…”
Section: Resultsmentioning
confidence: 99%
“…The lipolytic productivity (U/mL/h) was calculated according to the following Equation 3 (Burkert et al, 2005):…”
Section: Lipolytic Productivitymentioning
confidence: 99%
“…Burket et al and Maldonado et al showed that 3.58 % w/w of peptone is enough to obtain a high level of lipase activity from G. candidum. They demon- 52,61 . Ginalska et al showed that 0.4 % w/w of urea was the best condition of nitrogen source for lipase production compared to other organic sources.…”
Section: Production Of Geotrichum Spp Lipasesmentioning
confidence: 99%
“…Soybean oil also shows similar results due to its similar composition to olive oil, and its low cost is a strong appeal for its application. Concentrations of 1.0 % w/w are frequently utilized, but optimized studies showed that lower concentrations (0.5 to 0.7 % w/w) are enough to induce the lipase production, and concentrations above 1.0 % w/w do not have significant effects on the increase in lipase activity [52][53][54]56,[60][61][62] . Glucose is the most used carbon source for the growth of G. candidum and the utilized concentration is usually 1.0 % w/w.…”
Section: Production Of Geotrichum Spp Lipasesmentioning
confidence: 99%